Limited Open Reduction and Transepiphyseal Intramedullary Kirschner Wire Fixation for Treatment of Irreducible Distal Radius Diaphyseal Metaphyseal Junction Fracture in Older Children - Wang, Rufa; Wu, Liwei; Wang, Yinming; Fan, Minjie; Wang, Yiwei; Ning, Bo; Zheng, Pengfei (Frontiers in Pediatrics, 2022)
Objective This study aimed to compare limited open reduction and transepiphyseal intramedullary fixation with Kirschner wire (LOR-TIKW) versus open reduction and internal fixation with plate and screw (ORIF-PS) for treatment of irreducible distal radius diaphyseal–metaphyseal junction (DMJ) fracture in older children. Methods Data of children (aged 10–14 years) treated in our hospital for distal radius DMJ fractures with LOR-TIKW or ORIF-PS from January 2018 to December 2019 were retrospectively analyzed. Follow-up was until radiographic union. Demographic, clinical, and radiographic data; treatment cost; healing time; functional outcome (by Price criteria); complications; and postoperative angulation and displacement were compared between children treated by the two methods. Statistical analysis was performed with alpha set at P < 0.05. Results A total of 26 children were included: 14 treated with LOR-TIKW and 12 with ORIF-PS. Operation time was less (22.1 min vs. 46.7 min, P < 0.0001), surgical incision smaller (2.43 cm vs. 5.00 cm, P < 0.0001), cost of internal fixation lower (US$, 40.6 vs. 2020, P < 0.0001), and healing time shorter (4.79 weeks vs. 5.64 weeks, P = 0.03) with LOR-TIKW; however, postoperative fracture angulation was slightly larger (1.07° vs. 0.83°, P = 0.85) and displacement slightly more (0.86 mm vs. 0.58 mm, P = 0.44) in the LOR-TIKW group. Rate of union, functional outcome, and complications were not significantly different between the groups. Conclusion For irreducible DMJ fracture of distal radius in older children, LOR-TIKW appears to be a promising method with several advantages over ORIF-PS.